Implementasi Mind Mapping dalam Pembelajaran Sejarah Kebudayaan Islam di MA Syafa’aturrasul Kuantan Singingi Riau - Nurdini (ANWARUL, 2026)
Islamic Cultural History (SKI) instruction faces challenges in helping students understand extensive and interconnected content, particularly the Safavid Dynasty. Teacher-centered instruction causes students to experience difficulty identifying and systematically organizing important concepts. This study aimed to describe the implementation of the Mind Mapping method in SKI instruction on the Safavid Dynasty at Madrasah Aliyah Syafaaturrasul, Kuantan Singingi Regency, Riau. The study employed a qualitative approach with a descriptive design. The research informants comprised one SKI teacher, one vice principal for curriculum, and eight students, while the learning activities involved 20 students. Data were collected through observation, semi-structured interviews, and documentation and were subsequently analyzed using the Miles, Huberman, and Saldaña model through the stages of data condensation, data display, and conclusion drawing. The results showed that implementing Mind Mapping encouraged students’ active engagement, helped them organize information systematically, and facilitated their understanding of the material. The students responded positively and were able to produce mind maps containing the main concepts of the Safavid Dynasty. These findings confirm that Mind Mapping can be used as an alternative active, creative, and student-centered strategy for SKI instruction and can help teachers present complex historical material in a more structured and comprehensible manner.